EVALUATION OF BRAIN MICROGLIA PROLIFERATION AS A RESPONSE TO DBL2β-PFEMP1 RECOMBINANT PROTEIN IMMUNIZATION IN WISTAR RAT - Dewi, Rosita; Kusuma, Irawan Fajar; Sulistyaningsih , Erma; Rachmania, Sheilla; Luthfiyyah, Nur Atikah (MNJ (Malang Neurology Journal), 2025)
Background: In the malaria vaccine study, Duffy binding-like 2β Plasmodium falciparum erythrocyte membrane protein 1 (DBL2β-PfEMP1) could induce the  IgG and CD4+production. Antibody to DBL2β-PfEMP1 reduces the risk of developing severe malaria through the blockade of cytoadherence and destruction of rosette formation. During the process of antibody formation after immunization, the released peripheral cytokines have the potential to cause blood-brain barrier disruption resulting in the activation and proliferation of brain microglia as primary innate immune cells leading to neuroinflammation. Objective: This study aims to evaluate brain microglia proliferation as a response to recombinant protein DBL2β-PfEMP1 immunization in Wistar rats. Methods: Wistar rats were injected subcutaneously with recombinant protein DBL2β-PfEMP1 at doses of 100, 150, and 200 µg/kgBW on days 0, 21, and 42. Rats were euthanized on day 56. Brain histopathological slides were prepared and stained using hematoxylin-eosin. Histological examination was performed using a microscope at 400X magnification and documented using an AmScope microscope digital camera. Brain microglia were calculated using Fiji Image-J. The data were statistically analyzed using the Kruskal-Wallis test.  Results: The average number of brain microglia in both the control and treatment groups was 82–88. There was no significant difference in brain microglia number between the control and treatment groups (p>0.05) after recombinant protein DBL2β-PfEMP1 immunization. Conclusion: Recombinant protein DBL2β-PfEMP1 immunization does not provoke the proliferation of brain microglia in Wistar rats. This suggests that the protein does not have the potential to cause neuroinflammation.